Wearable Banking: A Study of Adoption Factors in Islamic Banking Institutions - Ali, Hafizi Muhamad; Shaari, Rohaya (Journal of University of Human Development, 2015)
Wearable banking has been coined by banking institutions in providing the latest technology to their customers. This study investigates the determinants which attract the Islamic banks’ customers to adopt wearable banking in Malaysia. The sample size of 350 respondents has been selected from ten Islamic banks in Malaysia using the survey research instrument questionnaire. Data has been analyzed using software SPSS 15.0. The confirmatory factor analysis with multiple regressions technique has been applied. The result of regression analysis shows that Perceived Usefulness, Information of Wearable Banking, Perceived Risk, Security and Privacy shows more influence in increasing the intention of customers to adopt wearable banking services. Meanwhile, Government Support provides more influence for the bankers in adoption of wearable banking services. This study proves that bankers should emphasize more on wearable banking, since bank customers believe it is a convenient method when adopting the banks services.